Comparison of immunoblotting (IgA and IgG) and the Goldmann-Witmer coefficient for diagnosis of ocular toxoplasmosis in immunocompetent patients. Issue 10 (17th January 2018) - Mathis, Thibaud; Beccat, Sylvain; Sève, Pascal; Peyron, François; Wallon, Martine; Kodjikian, Laurent
Abstract : Background: Ocular toxoplasmosis (OT) is a common cause of posterior uveitis worldwide. The diagnosis of OT is based on clinical findings, but in most cases, laboratory tests are required to confirm the aetiology, especially when other diseases are suspected. The aim of this study was to evaluate which methods, between the Goldmann-Witmer coefficient (GWC) and immunoblotting (IB) with both IgG and IgA, in aqueous humour (AH) samples, can be the most sensitive to diagnose OT, in current practice, especially in the first three weeks. Methods: Retrospectively reviewed records of 87 consecutive patients who had underwent AH and serum sample, 42 patients with suspected OT and 45 patients with suspected other ocular inflammatory diseases. All samples were analysed by both GWC and IB. Results: The GWC was significant in 47.6% of patients presenting with suspected OT. The intraocular production of specific antibody anti-Toxoplasma gondii IgG and IgA was revealed by IB in 71.4% of samples. The combination of these two methods increased the sensitivity to 76.2%. Based on the interval between symptom onset and paracentesis, IB had a greater sensitivity than GWC when sample of AH was taken in the first three weeks (64.7% vs 23.5%, P=0.039), while the difference between the sensitivity of IB and GWC was less important in cases with an interval >3 weeks (76% vs 64% P=0.625). Conclusion: IB seems to be more useful than the GWC if only one of these methods can be performed, especially during the first three weeks after symptom onset.